The integration of artificial intelligence technology in english language learning to enhance speaking skills through real-time feedback - Lina Herlina; Mashadi Said (Jurnal Konseling dan Pendidikan, 2026)
This research explores the integration of Artificial Intelligence (AI) technology in English language learning to enhance speaking skills through real-time feedback. The study addresses the limited effectiveness of conventional speaking instruction, which often lacks immediate correction and individualized practice. Using a Narrative Literature Review (NLR) approach, data were collected from books, academic journals, and scientific publications related to AI in education, real-time feedback, and speaking skill enhancement. The findings reveal that AI tools such as speech recognition systems and NLP-based chatbots significantly improve learners’ fluency, pronunciation, and confidence by providing instant, adaptive feedback. The study concludes that AI transforms traditional pedagogy into a dynamic, learner-centered model, fostering continuous improvement, engagement, and personalized learning experiences in developing English-speaking proficiency.